(untitled) (Al-Qamar, 2023)
The National Commission for Child Welfare and Development (NCCWD) was established by the Government of Pakistan on December 16, 1979, effective January 1, 1980, and amended several times until 1991. The Capital Administration and Development Division took over NCCWD ICT duties once the Ministry of Social Welfare and Special Education decentralized. On December 2, 2011, the Prime Minister authorized moving the Ministry of Human Rights. Human Rights oversees it. The NCCWD monitors and promotes UNCRC promises worldwide. The NCCWD informs the UN Committee on the Rights of the Child in Geneva and other interested parties on UN Convention implementation. how effective Pakistan has neglected child welfare, according to the report. The Convention on the Rights of the Child did not seem to promise help. In the last five years, not enough progress has been achieved to protect children’s rights in the areas of education, safety, and social welfare. Although protecting children’s social and security rights is vital, public discourse and policy debates have ignored it. Experts concluded from the research that Pakistan has not done enough for its children (Lansdown 2014).